Learning-Based Maritime Governance: Institutional Synergy and Maritime Domain Awareness in the Waters of Karimun Besar Island, Indonesia - Pulungan, Ahmad Ari Syahputra; Yusnaldi; Budiman Djoko Said (Cita konsultindo, 2025)
Indonesia’s maritime identity as the world’s largest archipelagic state places it at the center of global maritime trade and security dynamics. However, fragmented coordination among its maritime enforcement agencies—namely BAKAMLA, KPLP, and POLAIRUD—continues to limit effective governance, particularly in strategic regions such as Karimun Besar Island within the Malacca Strait. This study examines the problem of institutional synergy and Maritime Domain Awareness (MDA) through a learning-based governance perspective, employing a qualitative document analysis and triangulation approach. The research integrates three learning theories—Connectivism, Constructivism, and Social Learning Theory—to explore how inter-agency cooperation can evolve through digital connectivity, shared meaning, and behavioral adaptation. The findings reveal that Indonesia’s maritime security governance remains hindered by overlapping mandates, unintegrated information systems, and limited interoperability. Applying learning-based principles, the study argues that improving maritime synergy requires not only legal harmonization but also institutional learning through continuous data exchange, joint training, and shared operational frameworks. The paper proposes a National Maritime Security Coordination Framework that emphasizes data integration, collaborative learning, and adaptive policy reform. Strengthening institutional synergy and MDA through a learning-oriented approach is essential for realizing Indonesia’s vision as a Global Maritime Fulcrum, ensuring that its maritime governance becomes more coordinated, sustainable, and intelligence-driven.